Xenophobic attacks, migration intentions, and networks: Evidence from the South of Africa (2013)
We investigate how emigration from a developing region is affected by xenophobic violence at destination. Based on a unique household survey collected in Mozambique in summer 2008, a few months after a series of xenophobic attacks in South Africa that killed dozens and displaced thousands of immigrants from neighboring countries, we estimate migration intentions of Mozambicans before and after the attacks, controlling for a placebo period. We focus on the role of family and social networks in the sending community in shaping changes in the expressed intentions to migrate. We find that the migration intention of household heads decreases after the violence, especially for those household heads with many children whose families have no access to social networks. The results illustrate that networks at origin insure risks related to migration and that, when deciding to migrate, workers tend to care more about the future of their offspring than their own health. © 2012 Springer-Verlag Berlin Heidelberg.